Historical Pathways to Sovereignty Fakhr al‑Dīn II and the Arab Revolt in Policy Perspective - Kurniawan Arif Maspul; Hasbi Yusron (Indonesian Journal of Social Development, 2026)
This study examines two pivotal moments in Arab history—Emir Fakhr al-Dīn II’s 17th-century experiment in pluralist governance and the Arab Revolt of 1916–1918—as lenses through which to understand the ongoing struggle for sovereignty in the Middle East. Fakhr al-Dīn’s alliance with Renaissance Tuscany and his inclusive administration in Mount Lebanon demonstrate a practical model of statecraft based on commerce, tolerance, and institutional innovation. In contrast, the Arab Revolt, sparked by Sharif Husayn’s call for independence and driven by British promises, shows the danger of mobilising without solid guarantees. Both episodes, separated by centuries, focus on a common theme: the tension between local aspirations and imperial manipulation. Building on these histories, the paper outlines a seven-point policy framework for the Global South—highlighting pluralist governance, conditional foreign partnerships, formalised mediation, local capacity development, inclusive jurisprudence, evidence collection, and civic education. These lessons are not just ideals, but practical strategies to turn sovereignty from a symbolic goal into a lasting reality. The paper contends, by combining historical lessons with modern policy planning, that the path to legitimate governance is not through heroic moments or external pledges, but through the daily labour of creating inclusive institutions. This is more than just a historical reflection; it is a call to urgent statecraft for states facing geopolitical storms and the continuous struggle for dignity.